The Effect of Low Impact Aerobic Exercise on Elderly with Dementia Cognitive Function - Raden Ayu Tanzila; Sheilla Yonaka Lindri; Nindia Rahma Putri (Global Medical & Health Communication (GMHC), 2020)
In the elderly population, at least 10% of those over 65 years old and 50% of those over 80 years old experience a decline in cognitive function that varies from a cognitive decline due to normal aging (age-associated memory impairment/AAMI) to a mild cognitive decline (mild cognitive impairment/MCI) and dementia. Dementia is an intellectual disorder that affects the cognitive function, memory, language function, and visuospatial function that causes irreversible changes. Many studies have stated that lifestyle management in the form of increased physical activity has a protective effect on impaired cognitive functions, inhibits cognitive function decline, and even improves cognitive function in healthy elderly people and elderly with mild cognitive impairment to dementia. Low impact aerobic exercise is a physical activity that is useful and suitable for the elderly. This study aimed to determine the effect of low impact aerobic exercise on the cognitive function of elderly people with dementia. This was a quasi-experimental study with one group pretest-posttest method that involved elderly people from Tresna Werdha Teratai Palembang, South Sumatera, Indonesia who were selected based on the inclusion and exclusion criteria (n=38) from December 2018 to February 2019. Treatment provided was a low impact aerobic exercise 3 times a week for 5 weeks. Dementia was then measured before and after treatment using the Mini-mental State Examination (MMSE). The mean values of gymnastics before the treatment and after the treatment were 18.36±4.559 and 19.69±5.724, respectively. A p value of 0.000 was obtained using the Wilcoxon test. In summary, low impact aerobic exercise influences the cognitive function of the elderly with dementia. PENGARUH SENAM AEROBIK LOW IMPACT TERHADAP FUNGSI KOGNITIF USILA DENGAN DEMENSIAPada usia lanjut (usila), sedikitnya 10% dari yang berusia lebih dari 65 tahun dan 50% dari yang berusia lebih dari 80 tahun mengalami penurunan fungsi kognitif yang bervariasi mulai dari penurunan kognitif karena penuaan normal (age-associate memory impairment/AAMI) serta penurunan kognitif ringan (mild cognitive impairment/MCI) hingga demensia. Demensia adalah gangguan intelektual yang meliputi fungsi kognitif, daya ingat, bahasa, fungsi visuospasial, dan bersifat ireversibel. Banyak studi menyatakan bahwa manajemen gaya hidup berupa peningkatan aktivitas fisik mempunyai efek protektif terhadap gangguan fungsi kognitif, menghambat penurunan fungsi kognitif, serta bahkan meningkatkan fungsi kognitif pada usila yang sehat dan usila dengan penurunan fungsi kognitif ringan sampai demensia. Senam aerobik low impact merupakan aktifitas fisik yang bermanfaat dan cocok diberikan kepada usila. Penelitian ini bertujuan mengetahui pengaruh senam aerobik low impact terhadap fungsi kognitif usila dengan demensia. Penelitian ini merupakan studi quasi-experimental dengan metode pretest-posttest one group yang melibatkan usila dari Tresna Werdha Teratai Palembang, Sumatera Selatan, Indonesia yang dipilih berdasar atas kriteria inklusi dan eksklusi (n=38) dari bulan Desember 2018 hingga Februari 2019. Perlakuan yang diberikan berupa senam aerobik low impact 3 kali per minggu selama 5 minggu. Demensia kemudian diukur sebelum dan sesudah perlakuan menggunakan Mini-mental State Examination (MMSE). Nilai rerata senam sebelum perlakuan dan setelah perlakuan adalah 18,36±4,559 dan 19,69±5,724 masing-masing. Nilai p=0,000 didapatkan dengan menggunakan Uji Wilcoxon. Simpulan, senam aerobik low impact memengaruhi fungsi kognitif usila dengan demensia.